A wear-resistant alloy steel, plate hammer structure, crushing chamber structure for a crusher
Patent Information
- Application Number
- CN202610148629.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-03
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-02-03
AI Technical Summary
[0005]为解决上述现有技术中存在耐磨合金钢材料虽具有较高硬度和耐磨性,但其韧性较差的技术问题,本发明的目的在于提供一种破碎机用的耐磨合金钢、板锤结构、破碎腔结构,本发明在破碎机板锤用耐磨材料领域引入了全新的材料设计思路,通过将ZTA陶瓷颗粒复配于特定成分设计的耐磨合金钢基体中,构建金属—陶瓷颗粒复合耐磨材料体系,从材料体系和组织结构层面突破了传统高锰钢、高铬铸铁单一材料难以兼顾耐磨性与抗冲击性的技术局限
[0049]1.本发明提供了一种破碎机用的耐磨合金钢,用于反击式破碎机的板锤,所述耐磨合金钢为基体材料复配ZTA陶瓷颗粒制成,所述ZTA陶瓷颗粒在所述耐磨合金钢中的体积分数为20%~25%;其中,所述基体材料包括如下重量百分比的原料:C 0.50~0.55%;Si 0.9~1.2%;Mn 0.9~1.1%;Cr 0.9~1.2%;Mo 0.4~0.6%;Ni 1.6~1.8%;Nb 0.18%;余量为Fe。
Smart Images

Figure CN121951376B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of wear-resistant alloy steel, and more particularly to a wear-resistant alloy steel for crushers, a hammer structure, and a crushing chamber structure. Background Technology
[0002] Crushers are key equipment in industries such as mining, metallurgy, building materials, cement, sand and gravel aggregates, and solid waste treatment, and are widely used in crushing ores, rocks, construction waste, and various hard materials. Crushers operate under long-term, high-load, high-impact, and high-wear conditions. Their core vulnerable components (such as hammers and liners) typically need to withstand repeated impact loads, intense friction and wear, and complex stress alternation. Therefore, extremely high requirements are placed on the wear resistance, impact resistance, and structural stability of the materials used.
[0003] In existing technologies, wear-resistant parts of crushers are often made of high-manganese steel, high-chromium cast iron, ordinary alloy steel, or their composite materials. Among them, high-manganese steel relies on work hardening to improve wear resistance, but its work hardening is insufficient under low-impact or medium-low load conditions, resulting in severe initial wear. Although high-chromium cast iron has high hardness and wear resistance, its toughness is poor, and it is prone to cracking or fragmentation under strong impact conditions, limiting its application in high-impact crushing conditions. Although ordinary alloy steel materials have relatively balanced comprehensive performance, their wear life is still difficult to meet the actual needs of high-intensity, long-cycle continuous operation under long-term high-wear conditions.
[0004] With the increasing size of crushing equipment, the impact force on core components has increased, leading to a significant increase in wear and a marked shortening of service life, which has become a bottleneck in the development of crushing equipment. Therefore, it is necessary to develop new wear-resistant materials to improve the service life of key crusher components, reduce equipment maintenance frequency and operating costs, and meet the comprehensive requirements of modern crushing equipment for material performance under complex working conditions. Summary of the Invention
[0005] To address the technical problem in existing technologies where wear-resistant alloy steel materials possess high hardness and wear resistance but poor toughness, the present invention aims to provide a wear-resistant alloy steel, hammer structure, and crushing chamber structure for crushers. This invention introduces a novel material design approach to the field of wear-resistant materials for crusher hammers. By compounding ZTA ceramic particles into a wear-resistant alloy steel matrix with a specific composition design, a metal-ceramic particle composite wear-resistant material system is constructed. This overcomes the technical limitations of traditional high-manganese steel and high-chromium cast iron single materials, which struggle to simultaneously achieve both wear resistance and impact resistance, from the perspectives of material system and microstructure.
[0006] The objective of this invention is achieved through the following technical solution:
[0007] In a first aspect, the present invention provides a wear-resistant alloy steel for a crusher, specifically for the hammer of an impact crusher. The wear-resistant alloy steel is made by compounding a matrix material with ZTA ceramic particles, wherein the volume fraction of the ZTA ceramic particles in the wear-resistant alloy steel is 20%–25%. The matrix material comprises the following raw materials by weight percentage:
[0008] C 0.50~0.55%;
[0009] Si 0.9–1.2%;
[0010] Mn 0.9–1.1%;
[0011] Cr 0.9–1.2%;
[0012] Mo 0.4–0.6%;
[0013] Ni 1.6~1.8%;
[0014] Nb 0.18%;
[0015] The balance is Fe.
[0016] In conjunction with the first aspect, the present invention also provides a first specific embodiment of the first aspect, wherein preferably, the volume fraction of the ZTA ceramic particles is 25%; and the matrix material is composed of the following raw materials by weight percentage:
[0017] C 0.50%;
[0018] Si 1.0%;
[0019] Mn 1.0%;
[0020] Cr 1.1%;
[0021] Mo 0.5%;
[0022] Ni 1.7%;
[0023] Nb 0.18%;
[0024] The balance is Fe.
[0025] In conjunction with the first aspect, the present invention also provides a second specific embodiment of the first aspect, wherein preferably, the particle size of the ZTA ceramic particles is 1-2 mm, and the ZTA ceramic particles are pretreated and modified by the following method:
[0026] ZTA ceramic particles were placed in an ultrasonic cleaner and ultrasonically cleaned with anhydrous ethanol for 30 minutes. The cleaning was repeated 3 times.
[0027] After cleaning, the ZTA ceramic particles are placed in an oven for drying at 80°C for 1 hour.
[0028] Cleaned and dried ZTA ceramic particles, PVA binder, and Ti-Cu-Ni powder were added to a vibrating ball mill and mixed for 3 minutes to allow the Ti-Cu-Ni powder to adhere to and coat the surface of the ZTA ceramic particles. The amount of PVA binder added was 2.0 wt% of the mass of the ZTA ceramic particles, and the amount of Ti-Cu-Ni powder added was 8.0 wt% of the mass of the ZTA ceramic particles. The mass ratio of Ti, Cu, and Ni in the Ti-Cu-Ni powder was 4:3:3.
[0029] Alloy powder is prepared, wherein the raw materials and proportions of the alloy powder are the same as those of the matrix material; ZTA ceramic particles coated with Ti-Cu-Ni powder are mixed with the alloy powder in a vibrating ball mill for 3 minutes to further coat the outer layer of the ZTA ceramic particles with the alloy powder; wherein the alloy powder contains 8.0 wt% of the ZTA ceramic particles.
[0030] In conjunction with the first aspect, the present invention also provides a third specific embodiment of the first aspect, wherein, preferably, the wear-resistant alloy steel is prepared by the following method:
[0031] Step 1: Mix the pretreated and modified ZTA ceramic particles with the matrix material according to the preset ratio, and obtain composite powder after uniform mixing;
[0032] Step 2: The composite powder is loaded into the cavity of the pre-made mold and subjected to hot isostatic pressing at a temperature of 900℃ and a pressure of 150MPa to obtain a preliminary blank.
[0033] Step 3: The preliminary blank is sintered under an argon protective atmosphere at a sintering temperature of 1150℃ for 3 hours to obtain a sintered blank.
[0034] Step 4: Heat treatment of the sintered billet, including normalizing, quenching and tempering; specifically, normalizing involves heating to 1000℃, holding for 6 hours, and air cooling to room temperature; quenching involves heating to 900℃, holding for 6 hours, and then quenching with PAG quenching liquid; tempering involves tempering at 330℃, holding for 8 hours, and then air cooling to room temperature.
[0035] Secondly, the present invention also provides a hammer plate structure for an impact crusher, wherein the hammer plate structure is made of a wear-resistant alloy steel for a crusher as described in the first aspect and the first to third specific embodiments of the first aspect.
[0036] In conjunction with the second aspect, the present invention also provides a first specific embodiment of the second aspect, preferably, the hammer structure adopts a combined structure, including:
[0037] The hammer body is in the shape of a cuboid block, and has a stepped mounting part at the upper end of the hammer body, and a limiting groove is provided in the mounting part.
[0038] The wear-resistant part has a limiting part that is adapted to the limiting groove. The wear-resistant part is inserted into the limiting groove through the limiting part, and the wear-resistant part can also be fastened to the mounting part of the hammer body by bolts.
[0039] The hammer body and wear-resistant parts are both made of the wear-resistant alloy steel.
[0040] In conjunction with the second aspect, the present invention also provides a second specific embodiment of the second aspect. Preferably, the cross-sectional profile of the wear-resistant part is a right-angled trapezoidal shape, the wear-resistant part has an outer surface for contacting materials, and the outer surface of the wear-resistant part can be straight, inclined or curved; a wear-resistant coating is provided on the outer surface of the wear-resistant part.
[0041] In conjunction with the second aspect, the present invention also provides a third specific embodiment of the second aspect. Preferably, the wear-resistant coating is a gradient structure coating, and the wear-resistant coating has a bonding layer, a bearing layer and a wear-resistant layer formed sequentially by laser cladding process, wherein the bonding layer is connected to the outer surface of the wear-resistant part.
[0042] Thirdly, the present invention also provides a crushing chamber structure for use in an impact crusher, characterized in that the crushing chamber structure comprises:
[0043] The frame includes an upper frame and a lower frame that are arranged to cooperate with each other. One side of the lower frame is open, and the upper frame is detachably installed at the opening of the lower frame. The upper frame and the lower frame are closed to form a crushing chamber, which has a material inlet end and a material outlet end.
[0044] The rotor assembly includes a rotor and a plurality of hammer plates. The rotor is rotatably mounted on the lower frame and located in the crushing chamber. The plurality of hammer plates are detachably mounted on the rotor and are evenly distributed along the circumference of the rotor. The hammer plates adopt the hammer plate structure described in the second aspect and the first to third specific embodiments of the second aspect.
[0045] The impact plate assembly includes multiple impact frames and multiple impact plates connected to the impact frames; the multiple impact frames are arranged sequentially along the outer circumferential surface of the rotor; the multiple impact plates are arranged at intervals along the outer circumferential direction of the rotor, and a crushing chamber is formed between the multiple impact plates and the rotor.
[0046] In conjunction with the third aspect, the present invention also provides a first specific embodiment of the third aspect, wherein, preferably, the impact plate assembly includes three impact frames arranged sequentially along the direction from the material feed end to the material discharge end, and the lengths of the three impact frames decrease sequentially along the direction from the material feed end to the material discharge end.
[0047] The impact plates installed on each impact frame are arranged in a logarithmic spiral shape with the axis of the rotor as the center, so that multiple impact plates gradually approach the outer circumference of the rotor along the direction from the material feed end to the material discharge end, thereby forming a cavity structure in which the crushing chamber gradually contracts from the feed end to the discharge end.
[0048] Compared with the prior art, the present invention has at least the following beneficial effects:
[0049] 1. This invention provides a wear-resistant alloy steel for crushers, specifically for the hammer of an impact crusher. The wear-resistant alloy steel is made of a matrix material compounded with ZTA ceramic particles, wherein the volume fraction of the ZTA ceramic particles in the wear-resistant alloy steel is 20%–25%. The matrix material comprises the following raw materials by weight percentage: C 0.50–0.55%; Si 0.9–1.2%; Mn 0.9–1.1%; Cr 0.9–1.2%; Mo 0.4–0.6%; Ni 1.6–1.8%; Nb 0.18%; with the balance being Fe.
[0050] This invention introduces a novel material design approach to the field of wear-resistant materials for crusher hammers. By compounding ZTA ceramic particles into a wear-resistant alloy steel matrix with a specific composition, a metal-ceramic particle composite wear-resistant material system is constructed. The volume fraction of ZTA ceramic particles is set at 20%–25%, significantly increasing the content of the hard phase while maintaining overall toughness. Simultaneously, through the synergistic design of multiple alloying elements such as C, Cr, Mo, Ni, and Nb, an alloy steel matrix with high strength, high toughness, and good interfacial bonding is formed. This breakthrough overcomes the technical limitations of traditional high-manganese steel and high-chromium cast iron single materials, which struggle to simultaneously achieve wear resistance and impact resistance, at the material system and microstructure levels.
[0051] 2. This invention also provides specific applications of wear-resistant alloy steel for crushers, offering a hammer plate structure and a crushing chamber structure for an impact crusher. Thanks to the high hardness and toughening properties of ZTA ceramic particles and the effective buffering effect of the alloy steel matrix on impact loads, the wear rate can be significantly reduced under the high impact and high wear conditions of the impact crusher hammer. Attached Figure Description
[0052] Figure 1 This is a schematic diagram of the impact crusher provided by the present invention;
[0053] Figure 2A schematic diagram of the AA section of the crushing chamber structure provided by the present invention;
[0054] Figure 3 This is a three-dimensional schematic diagram of the hammer structure provided by the present invention;
[0055] Figure 4 This is an assembly diagram of the hammer plate structure provided by the present invention;
[0056] In the picture:
[0057] 10- Impact crusher;
[0058] 100-Hammer structure, 110-Hammer body, 111-Mounting part, 112-Limiting groove, 120-Wear-resistant part, 121-Limiting part;
[0059] 200-Counterattack plate assembly. Detailed Implementation
[0060] To facilitate understanding of the present invention, the technical solutions and advantages of the invention will be further described in detail below with reference to the accompanying drawings and embodiments. Any mechanisms or methods not elaborated in this invention can be referred to in the prior art. The specific structures and features of the present invention are illustrated below by way of example and should not be construed as limiting the present invention in any way. Furthermore, any of the technical features mentioned below (including implicit or disclosed features), as well as any technical features directly shown or implied in the figures, can be arbitrarily combined or deleted among these technical features to form more other embodiments that may not be directly or indirectly mentioned in this invention. The accompanying drawings show preferred embodiments of the present invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0061] In existing technologies, wear-resistant parts of crushers are often made of high-manganese steel, high-chromium cast iron, ordinary alloy steel, or their composite materials. Among them, high-manganese steel relies on work hardening to improve wear resistance, but its work hardening is insufficient under low-impact or medium-low load conditions, resulting in severe initial wear. Although high-chromium cast iron has high hardness and wear resistance, its toughness is poor, and it is prone to cracking or fragmentation under strong impact conditions, limiting its application in high-impact crushing conditions. Although ordinary alloy steel materials have relatively balanced comprehensive performance, their wear life is still difficult to meet the actual needs of high-intensity, long-cycle continuous operation under long-term high-wear conditions.
[0062] With the increasing size of crushing equipment, the impact force on core components has increased, leading to a significant increase in wear and a marked shortening of service life, which has become a bottleneck in the development of crushing equipment. Therefore, it is necessary to develop new wear-resistant materials to improve the service life of key crusher components, reduce equipment maintenance frequency and operating costs, and meet the comprehensive requirements of modern crushing equipment for material performance under complex working conditions.
[0063] Therefore, this invention provides a wear-resistant alloy steel for crushers, specifically for the hammer of an impact crusher. The wear-resistant alloy steel is made by compounding ZTA ceramic particles into the matrix material. This invention introduces a novel material design concept into the field of wear-resistant materials for crusher hammers. By compounding ZTA ceramic particles into a wear-resistant alloy steel matrix with a specific composition design, a metal-ceramic particle composite wear-resistant material system is constructed. The volume fraction of ZTA ceramic particles is set at 20%–25%, significantly increasing the content of the hard phase while maintaining overall toughness. Simultaneously, through the synergistic design of multiple alloying elements such as C, Cr, Mo, Ni, and Nb, an alloy steel matrix with high strength, high toughness, and good interfacial bonding ability is formed. This overcomes the technical limitations of traditional high-manganese steel and high-chromium cast iron single materials, which struggle to simultaneously achieve wear resistance and impact resistance, from the perspectives of material system and microstructure.
[0064] Specifically, the present invention provides a wear-resistant alloy steel for crushers, which is made of a matrix material compounded with ZTA ceramic particles. The volume fraction of ZTA ceramic particles in the wear-resistant alloy steel is 20% to 25%.
[0065] The matrix material comprises the following raw materials by weight percentage:
[0066] C 0.50~0.55%;
[0067] Si 0.9–1.2%;
[0068] Mn 0.9–1.1%;
[0069] Cr 0.9–1.2%;
[0070] Mo 0.4–0.6%;
[0071] Ni 1.6~1.8%;
[0072] Nb 0.18%;
[0073] The balance is Fe.
[0074] In the embodiments of this application, the microstructure of the wear-resistant alloy steel mainly includes: an iron-based matrix structure with tempered martensite as the main component, and the phases in the matrix mainly consist of tempered martensite, retained austenite, and carbides, for example, , and Carbides, including niobium carbide, which contains elongated carbides. High-hardness ZTA ceramic particles distributed in the matrix; dispersed carbide phases formed by elements such as Cr, Mo, and Nb.
[0075] In this invention, the synergistic reinforcement effect of iron-based alloying elements with ZTA ceramic particles is achieved through a reasonable ratio: (1) C, Cr, Mo: promote the formation of high-hardness carbides and improve the wear resistance of the matrix. (2) Ni, Mn: significantly improve the toughness and impact resistance of the matrix and compensate for the brittleness risk that may be brought about by the introduction of ceramic phase. (3) Nb: refines the grains and forms stable NbC carbides, inhibits grain boundary weakening, and improves the structural stability under high load conditions. After adding Nb, the microstructure is refined, and fine NbC reinforcing particles are dispersed in the matrix. Combined with the fine grain strengthening and second phase strengthening mechanisms, the strength, hardness, impact toughness and wear resistance of the wear-resistant alloy steel are improved.
[0076] Through the combined effect of the aforementioned alloying elements, the matrix material maintains high hardness while also possessing good impact resistance, thus adapting to the complex service environment of "strong impact + strong wear" under crusher operating conditions.
[0077] As the volume fraction of ceramic particles in composite materials increases, the wear resistance of the composite material initially increases and then decreases, indicating an optimal value for the ceramic particle volume fraction that maximizes the wear resistance. Generally speaking, if the volume fraction of ceramic particles in the composite material is large, the tendency for the composite material to crack during service wear will also increase.
[0078] In this embodiment, the volume fraction of ZTA ceramic particles in the overall material is 20% to 25%. This volume fraction range is used to ensure a significant improvement in wear resistance while also taking into account the overall toughness, impact resistance, and casting stability of the material.
[0079] Specifically, ZTA ceramic is a multiphase ceramic material with alumina as the main component and toughened by zirconia phase transformation, possessing both high hardness and a certain degree of fracture toughness. With increasing particle size, at the same volume fraction, larger ZTA ceramic particles result in a lower particle count, fewer introduced defects, higher composite density, and higher impact toughness. At the same volume fraction, larger ZTA ceramic particles also result in greater inter-particle distance, increasing the spatial distance at which the matrix exerts its toughness effect, thus increasing impact toughness. As the volume fraction increases, the influence of particle size decreases. With a higher volume fraction, the inter-particle distance decreases significantly, and some particles may aggregate. At this point, the influence of ZTA ceramic particle size diminishes, and volume fraction becomes the primary influencing factor.
[0080] In this invention, ZTA ceramic particles are introduced into the iron-based wear-resistant alloy at a volume fraction of 20% to 25%, and their main mechanism of action includes:
[0081] (1) Hard phase support: ZTA ceramic particles have a significantly higher hardness than iron-based alloy matrix. Under abrasive wear and impact wear conditions, ceramic particles preferentially bear the cutting and impact loads of external abrasive particles, reducing the direct wear degree of matrix material, thereby significantly improving the wear resistance of composite materials.
[0082] (2) Wear path blocking effect: ZTA ceramic particles dispersed in the matrix change the propagation path of wear cracks and microcracks, causing the cracks to deflect, bifurcate or terminate during propagation, inhibiting the formation of continuous cracks and delaying the material failure process.
[0083] (3) Interface layer buffering and stress transition: Combined with the aforementioned pretreatment modification and preparation process, a stable interface layer is formed between ZTA ceramic particles and the matrix. This interface layer plays a role in stress buffering and performance transition between the ceramic phase and the metal phase, reducing the interface stress concentration caused by the difference in elastic modulus and thermal expansion coefficient.
[0084] In summary, within the volume fraction range of 20% to 25%, by rationally selecting the ceramic particle size, interface modification method, and toughness matrix composition design, the composite material can achieve significant wear resistance enhancement while still maintaining good impact resistance.
[0085] In a preferred embodiment, the ZTA ceramic particles have a particle size range of 1–2 mm and can be spherical. The technical parameters of the ZTA ceramic particles are as follows:
[0086] ZTA 4.3 1500~1700 ~9.2 240
[0087] The particle size of ZTA ceramic particles is limited to the range of 1-2 mm, mainly based on the following technical considerations:
[0088] (1) Balancing wear resistance enhancement and structural stability: When the particle size of ZTA ceramic particles is less than 1 mm, the bearing capacity of a single particle for abrasive wear and impact load is limited, and it is easy to wear synchronously with the matrix under high impact conditions, and the enhancement effect is not obvious; when the particle size is greater than 2 mm, the stress concentration at the interface between the particles and the metal matrix is significantly enhanced, and it is easy to form interface debonding or macro cracks under impact load, affecting the overall structural stability.
[0089] (2) Load scale suitable for typical working conditions of crusher: This particle size range matches the impact energy and abrasive size borne by the crusher hammer, liner and other components in actual operation, so that ceramic particles can effectively share the impact and wear load at the micro and meso scales.
[0090] (3) The surface curvature of spherical particles is uniform, and the stress distribution is relatively uniform under external load. This can effectively reduce stress concentration at sharp corners and improve overall impact resistance and stability. It is suitable for crushing conditions with large impact loads.
[0091] Interfaces in composite materials play a crucial role in transferring the mechanical properties between the matrix material and the reinforcing phase. The bonding state and strength of the composite material interface directly affect its overall performance. A good interface can effectively transfer loads, protect reinforcing particles, and prevent crack initiation and propagation. For wear-resistant composite materials, the interfacial layer of particle-reinforced metal matrix composites is typically very narrow and unevenly distributed around the particles, resulting in a complex mechanical environment around the interfacial layer. The bonding state of the interface has a significant impact on the strength, toughness, and wear resistance of the composite material. The interfacial bonding strength of composite materials is closely related to the shape and size of the particles and the compatibility between the particles and the matrix.
[0092] Therefore, this application also provides a pretreatment modification of ZTA ceramic particles, which is performed by the following method:
[0093] Step (1): Place the ZTA ceramic particles into an ultrasonic cleaner and perform ultrasonic cleaning with anhydrous ethanol for 30 minutes. Repeat the cleaning process 3 times.
[0094] Step (2): After cleaning, place the ZTA ceramic particles in an oven for drying at 80℃ for 1 hour.
[0095] Step (3): Add the cleaned and dried ZTA ceramic particles, PVA binder, and Ti-Cu-Ni powder to a vibrating ball mill and mix for 3 minutes to allow the Ti-Cu-Ni powder to adhere to and coat the surface of the ZTA ceramic particles; wherein, the amount of PVA binder added is 2.0 wt% of the mass of the ZTA ceramic particles; the amount of Ti-Cu-Ni powder added is 8.0 wt% of the mass of the ZTA ceramic particles, and the mass ratio of Ti, Cu, and Ni in the Ti-Cu-Ni powder is 4:3:3.
[0096] Step (4): Prepare alloy powder, wherein the raw materials and proportions of the alloy powder are the same as those of the matrix material; mix the ZTA ceramic particles coated with Ti-Cu-Ni powder and the alloy powder in a vibrating ball mill for 3 minutes to further coat the outer layer of the ZTA ceramic particles with the alloy powder; wherein the alloy powder is 8.0 wt% of the mass of the ZTA ceramic particles.
[0097] Understandably, through the aforementioned pretreatment modification steps, a structure is constructed on the surface of ZTA ceramic particles, consisting of, from the inside out: the ZTA ceramic particle body, a Ti-Cu-Ni active metal transition layer, and an alloy outer layer with the same composition as the matrix material. In the Ti-Cu-Ni transition layer, Ti has strong activity, which can promote the chemical bonding between ceramic and metal at the interface; Ni can improve the wettability between the particles and the matrix; and Cu can lower the melting point of the mixed powder, promote diffusion between elements, and help form a diffusion layer at the interface. The synergistic effect of these three elements makes it easier for ZTA ceramic particles to be stably coated by the metal matrix during casting or composite processes. Furthermore, by using alloy powder with the same composition as the matrix material for secondary coating, the outer layer of the ceramic particles can achieve compositional homogeneity fusion with the matrix during subsequent forming processes, significantly reducing the risk of interface debonding and improving the long-term service stability of the ceramic particles under high impact loads.
[0098] Scanning electron microscopy (SEM) analysis revealed that the pretreated and modified ZTA ceramic particles were more uniformly dispersed in the matrix material, and the bonding between the particles and the matrix interface was significantly better. No obvious pores or defects were observed at the composite material interface, and the number of interface defects was significantly reduced compared to before modification. Magnified observation of the interface in the microstructure of the wear-resistant alloy steel revealed a distinct interface layer between the ZTA ceramic particles and the matrix. The phases of this interface layer were distributed at the grain boundaries of the matrix material, exhibiting a discontinuous distribution. The interface phases were densely bonded to the grain boundaries of both the ZTA ceramic particles and the matrix material. Furthermore, EDS analysis using the accompanying SEM showed that Al, Zr, and O elements from the ZTA ceramic particles diffused towards the interface, while Fe and Cr from the matrix material underwent metallurgical bonding at the interface, reducing porosity caused by poor wettability between the ZTA ceramic particles and the matrix material.
[0099] It should be noted that this application is not a simple routine cleaning process for ceramic particles, but rather a multi-stage pretreatment modification design of "cleaning and activation + active metal transition layer + homogeneous alloy outer layer" that systematically solves the interfacial bonding problem in ceramic particle-reinforced metal materials: the selection of the Ti-Cu-Ni ternary active system and its mass ratio have a clear functional division; the multi-layer coating structure forms a stable gradient transition interface in the material system.
[0100] In one specific embodiment, this application also provides a process for preparing wear-resistant alloy steel, which is prepared by the following method:
[0101] Step (1): Mix the pretreated and modified ZTA ceramic particles with the matrix material according to the preset ratio, and obtain composite powder after uniform mixing.
[0102] In this step, the chemical composition and proportion of the matrix material are the same as those of the modified and pretreated alloy powder in the previous embodiments. By surface-coating and modifying the ZTA ceramic particles, they can maintain good dispersibility during mixing with the matrix material, avoiding particle agglomeration, thereby obtaining a composite powder system with uniform composition distribution.
[0103] Step (2): The composite powder is loaded into the cavity of the pre-made mold and subjected to hot isostatic pressing at a temperature of 900℃ and a pressure of 150MPa to obtain a preliminary blank.
[0104] Through hot isostatic pressing, the composite powder is fully densified under the combined action of high temperature and isotropic pressure, significantly reducing porosity and enabling ZTA ceramic particles to achieve close contact with the matrix material at both the macroscopic and microscopic scales, laying the foundation for subsequent sintering and metallurgical bonding.
[0105] Step (3): The preliminary blank is sintered under an argon protective atmosphere at a sintering temperature of 1150℃ for 3 hours to obtain a sintered blank.
[0106] High-temperature sintering under an inert atmosphere can effectively prevent oxidation of the metal matrix and coating layer, while promoting atomic diffusion and interfacial metallurgical bonding within the matrix material, thus forming a stable interfacial structure between ZTA ceramic particles and the matrix material.
[0107] Step (4): Heat treatment of the sintered billet, including normalizing, quenching and tempering; wherein, normalizing is heating to 1000℃, holding for 6 hours, and air cooling to room temperature; quenching is heating to 900℃, holding for 6 hours and then quenching with PAG quenching liquid; tempering temperature is 330℃, holding for 8 hours and air cooling to room temperature.
[0108] The sintered billet is heated to 1000℃ and held for 6 hours by normalizing, followed by air cooling to room temperature to refine the grains, homogenize the microstructure, and eliminate internal stress. The normalized billet is then reheated to 900℃ and held for 6 hours by quenching, followed by quenching with PAG quenching fluid to obtain a high-hardness martensitic microstructure. Finally, the quenched billet is heated to 330℃ and held for 8 hours by tempering, followed by air cooling to room temperature to eliminate quenching stress and improve the material's toughness, enabling the wear-resistant alloy steel to maintain high hardness while possessing good impact resistance.
[0109] Through the above preparation process, the wear-resistant alloy steel prepared in the embodiments of this application has a dense structure, low porosity, and stable overall mechanical properties; the ZTA ceramic particles are evenly distributed, the interface is firmly bonded, and it is not easy to peel off; at the same time, it has excellent wear resistance and impact resistance; it is particularly suitable for high impact and high wear conditions such as crusher hammers and liners.
[0110] In summary, compared with existing single high-manganese steel, high-chromium cast iron, or simple alloy steel materials, the wear-resistant alloy steel of this invention has at least the following beneficial effects: It significantly improves wear life under high-impact and high-abrasive wear conditions; it avoids the problems of high brittleness and easy overall fracture of single ceramic materials; it balances wear resistance and impact resistance, reducing abnormal failures of components such as crusher hammers and liners; and it helps extend the replacement cycle of key crusher components, reducing downtime maintenance costs.
[0111] To further illustrate the present invention, based on the above-described technical solution, the following detailed description of a wear-resistant alloy steel for crushers provided by the present invention is provided in conjunction with embodiments, but it should not be construed as a limitation on the scope of protection of the present invention.
[0112] Example 1
[0113] This embodiment 1 provides a wear-resistant alloy steel for crushers, which is made of a matrix material compounded with ZTA ceramic particles. The volume fraction of ZTA ceramic particles in the wear-resistant alloy steel is 20%, and the ZTA ceramic particles have undergone the pretreatment modification described above.
[0114] The matrix material comprises the following raw materials by weight percentage:
[0115] C 0.50%;
[0116] Si 0.9%;
[0117] Mn 0.9%;
[0118] Cr 0.9%;
[0119] Mo 0.4%;
[0120] Ni 1.6%;
[0121] Nb 0.18%;
[0122] Fe 94.62%.
[0123] Example 1 of this application also provides a process for preparing wear-resistant alloy steel, which is prepared by the following method:
[0124] Step (1): Mix the pretreated and modified ZTA ceramic particles with the matrix material according to the preset ratio, and obtain composite powder after uniform mixing.
[0125] Step (2): The composite powder is loaded into the cavity of the pre-made mold and subjected to hot isostatic pressing at a temperature of 900℃ and a pressure of 150MPa to obtain a preliminary blank.
[0126] Step (3): The preliminary blank is sintered under an argon protective atmosphere at a sintering temperature of 1150℃ for 3 hours to obtain a sintered blank.
[0127] Step (4): Heat treatment of the sintered billet, including normalizing, quenching and tempering; wherein, normalizing is heating to 1000℃, holding for 6 hours, and air cooling to room temperature; quenching is heating to 900℃, holding for 6 hours and then quenching with PAG quenching liquid; tempering temperature is 330℃, holding for 8 hours and air cooling to room temperature.
[0128] Example 2
[0129] This embodiment 2 provides a wear-resistant alloy steel for crushers, which is made of a matrix material compounded with ZTA ceramic particles. The volume fraction of ZTA ceramic particles in the wear-resistant alloy steel is 25%, and the ZTA ceramic particles have undergone the pretreatment modification described above.
[0130] The matrix material comprises the following raw materials by weight percentage:
[0131] C 0.5%;
[0132] Si 1.0%;
[0133] Mn 1.0%;
[0134] Cr 1.1%;
[0135] Mo 0.5%;
[0136] Ni 1.7%;
[0137] Nb 0.18%;
[0138] Fe 94.02%.
[0139] Example 2 of this application also provides a process for preparing wear-resistant alloy steel, which is prepared by the following method:
[0140] Step (1): Mix the pretreated and modified ZTA ceramic particles with the matrix material according to the preset ratio, and obtain composite powder after uniform mixing.
[0141] Step (2): The composite powder is loaded into the cavity of the pre-made mold and subjected to hot isostatic pressing at a temperature of 900℃ and a pressure of 150MPa to obtain a preliminary blank.
[0142] Step (3): The preliminary blank is sintered under an argon protective atmosphere at a sintering temperature of 1150℃ for 3 hours to obtain a sintered blank.
[0143] Step (4): Heat treatment of the sintered billet, including normalizing, quenching and tempering; wherein, normalizing is heating to 1000℃, holding for 6 hours, and air cooling to room temperature; quenching is heating to 900℃, holding for 6 hours and then quenching with PAG quenching liquid; tempering temperature is 330℃, holding for 8 hours and air cooling to room temperature.
[0144] Example 3
[0145] This embodiment 3 provides a wear-resistant alloy steel for crushers, which is made of a matrix material compounded with ZTA ceramic particles. The volume fraction of ZTA ceramic particles in the wear-resistant alloy steel is 24%, and the ZTA ceramic particles have undergone the pretreatment modification described above.
[0146] The matrix material comprises the following raw materials by weight percentage:
[0147] C 0.55%;
[0148] Si 1.2%;
[0149] Mn 1.1%;
[0150] Cr 1.2%;
[0151] Mo 0.6%;
[0152] Ni 1.8%;
[0153] Nb 0.18%;
[0154] Fe 93.37%.
[0155] Example 3 of this application also provides a process for preparing wear-resistant alloy steel, which is prepared by the following method:
[0156] Step (1): Mix the pretreated and modified ZTA ceramic particles with the matrix material according to the preset ratio, and obtain composite powder after uniform mixing.
[0157] Step (2): The composite powder is loaded into the cavity of the pre-made mold and subjected to hot isostatic pressing at a temperature of 900℃ and a pressure of 150MPa to obtain a preliminary blank.
[0158] Step (3): The preliminary blank is sintered under an argon protective atmosphere at a sintering temperature of 1150℃ for 3 hours to obtain a sintered blank.
[0159] Step (4): Heat treatment of the sintered billet, including normalizing, quenching and tempering; wherein, normalizing is heating to 1000℃, holding for 6 hours, and air cooling to room temperature; quenching is heating to 900℃, holding for 6 hours and then quenching with PAG quenching liquid; tempering temperature is 330℃, holding for 8 hours and air cooling to room temperature.
[0160] Furthermore, this application also conducts corresponding product tests on the above-described Embodiments 1, 2, and 3. The test process is as follows:
[0161] I. Sample Preparation
[0162] The wear-resistant alloy steels prepared in Examples 1 to 3 were machined to obtain steel block samples with dimensions of 130×130×80mm.
[0163] II. Mechanical Property Testing
[0164] 2.1 Rockwell Hardness Test
[0165] The steel block sample was subjected to Rockwell hardness testing using an HBRVU-187.5 Brinell hardness tester, set to 1471 N (150 kg). A 63.5 HRC standard test block was used for calibration before testing. Twelve points were randomly marked on the test surface for hardness testing. After loading for 15 seconds, the load was removed, and the maximum and minimum values were discarded. The average value was then taken as the final Rockwell hardness value for the sample.
[0166] 2.2 Micro Vickers Hardness Test
[0167] The matrix hardness of the steel block sample was tested using a digital microhardness tester HXD-1000TMSC / LCD. The parameters were set with a load of 200GF and a loading time of 15s. Calibration was performed using a 753HV standard sample before testing. Twelve points were randomly selected on the test surface of the matrix for microVickers hardness testing. The maximum and minimum values were removed, and the average value was taken to obtain the final microVickers hardness value of the sample matrix.
[0168] 2.3 Impact toughness test
[0169] The steel block samples from Examples 1 to 3 were made into standard 10×10×55mm rectangular samples. The standard Charpy V-notch impact test specimens were tested using a JBW-300HC instrumented metal pendulum impact testing machine. Each type of steel block sample was tested three times and the average value was taken to obtain the impact absorbed energy.
[0170] 2.4 Tensile test
[0171] Tensile tests were performed on the specimens using an MTS electronic universal testing machine at room temperature and a tensile rate of 0.05 mm / min. Each specimen was tested three times, and the average of the three tensile strengths was taken as the final tensile strength.
[0172] Specifically, the test results are shown in the table below:
[0173] Example 1 60.4 678.3 8.6 1957.6 Example 2 60.9 682.2 9.1 1982.5 Example 3 60.6 680.5 8.9 1965.6
[0174] III. Impact Abrasive Wear Test
[0175] To investigate the resistance of wear-resistant alloy steel to abrasive wear under impact loads, an MLD-10B impact abrasive wear testing machine was used to study the material's impact wear resistance. The MLD-10B dynamic load abrasive wear testing machine mainly consists of a hammer, an upper specimen, a lower specimen, and a funnel. The hammer weighs 10 kg, and the steel specimen to be impacted is fixed at the bottom of the hammer, which drives the impact on the friction pair. The impact energy for abrasive wear is adjusted by changing the height of the hammer's fall. SiO2 abrasive flows from the funnel next to the lower specimen, and, in conjunction with the reciprocating impact motion of the hammer, achieves impact abrasive wear on the friction pair and the upper specimen.
[0176] In the experiments conducted in this application, the friction pair was made of quenched alloy steel (Cr12MoV, hardness 58HRC), and the rotation speed was 200 revolutions per minute. The abrasive was 20-40 mesh quartz sand with an irregular pointed shape, a flow rate of 50 kg / h, and an impact frequency of 150 times / minute. Before and after wear, the samples were ultrasonically cleaned for five minutes and dried in a drying oven at 100°C. After one hour of drying, the weight of the samples was measured. After 30 minutes of pre-grinding, a 150-minute impact abrasive wear test was conducted. The mass loss of each sample before and after impact abrasive wear was calculated. Each sample was measured five times, and the average value was taken as the final measurement result.
[0177] Specifically, the test results are shown in the table below:
[0178] Wear amount / g 0.1251 0.1176 0.1192
[0179] The above experimental results show that the wear-resistant alloy steels prepared in Examples 1-3 of this application all exhibit low mass loss under impact abrasive wear conditions, indicating that the materials possess good resistance to impact abrasive wear. Combined with the aforementioned microstructure analysis, it is evident that the uniform dispersion of ZTA ceramic particles in the matrix and the dense interfacial bonding effectively suppress the spalling of ceramic particles and the propagation of interfacial cracks during wear. Under impact loads, ZTA ceramic particles preferentially bear the abrasive cutting and impact energy, while the ductile iron matrix absorbs impact stress; both work synergistically to reduce the overall wear rate of the material. The small difference in wear amount among the various examples indicates that the technical solution described in this application has good process stability and performance consistency.
[0180] Based on the above technical solutions and the results of impact abrasive wear tests, the excellent wear resistance of the wear-resistant alloy steel of this invention mainly stems from the synergistic reinforcement effect of the matrix material and ZTA ceramic particles: the wear-resistant alloy steel matrix, mainly composed of tempered martensite, maintains high hardness while possessing good impact resistance, providing stable structural support for the material under repeated impact loads; the high-hardness ZTA ceramic particles preferentially bear abrasive cutting and impact loads during wear, significantly reducing direct wear of the matrix, and delaying material failure by blocking and deflecting wear cracks; controlling the volume fraction of ZTA ceramic particles within the range of 20% to 25% ensures a balance between the ceramic reinforcement effect and the continuity and toughness of the matrix, avoiding brittle failure caused by excessive particles; simultaneously, through the multi-level interface modification structure of "Ti-Cu-Ni active transition layer + homogeneous alloy outer layer", the interfacial bonding strength and stress transition capacity between ceramic particles and the matrix are effectively improved, suppressing particle debonding and interface crack propagation under impact conditions. The synergistic effect of these multiple mechanisms enables the material to maintain stable and low-speed wear behavior under conditions of strong impact and strong abrasive wear, thereby achieving significantly better impact and abrasive wear resistance than traditional wear-resistant materials.
[0181] Based on the above-mentioned wear-resistant alloy steel, this application embodiment also provides a practical application scenario for wear-resistant alloy steel, applied to an impact crusher. Specifically, the hammer structure of the impact crusher is integrally made of the wear-resistant alloy steel for crushers described in any of the above embodiments.
[0182] Understandably, this hammer structure is used in impact crushers, primarily to impact and crush materials. The working principle of an impact crusher relies on the repeated impact of the hammer with the material to break it into the required particle size. Because the working environment of an impact crusher is extremely harsh, the hammer must withstand the dual challenges of high impact loads and severe wear. Therefore, selecting suitable wear-resistant materials for the hammer is crucial for improving the crusher's working efficiency and extending its service life.
[0183] Since impact crushers are mainly used for crushing materials such as ores, sand, gravel, and construction waste, their hammers need to work for a long time under high impact and high wear conditions.
[0184] In this embodiment, the hammer structure directly withstands high-frequency impact loads and severe abrasive wear from materials during operation. Its service environment is characterized by high impact energy, strong load fluctuations, and complex wear patterns. By applying the aforementioned wear-resistant alloy steel with ZTA ceramic particles to the hammer structure, the hammer simultaneously possesses high hardness, high strength, and good impact toughness at the structural level. Therefore, the hammer structure can effectively extend its service life during long-term operation of the impact crusher, reduce the risk of fracture and abnormal failure, decrease the frequency of downtime for replacement, and significantly improve the operational reliability and economy of the crushing equipment.
[0185] In actual production operations, the speed and ease of hammer replacement are crucial factors affecting the crusher's production efficiency. Disassembling worn hammers or replacing them with new ones requires significant time and manpower, as well as complex dynamic balancing checks. Replacing a set of hammers typically takes at least one shift, reducing crushing output and increasing costs. Hammer wear in impact crushers only occurs on the side facing the material, with minimal wear on the back and sides. Hammers need replacement even with minimal wear, resulting in low metal utilization.
[0186] Therefore, this invention provides an innovative impact crusher hammer structure. By adopting a combined structure, the wear-resistant parts and the hammer body can be replaced independently, which not only reduces the difficulty and time of replacement but also improves the utilization rate of metal materials and extends the service life of the hammer. This design effectively improves the working efficiency of the crusher, reduces maintenance costs, and has strong application prospects and promotional value.
[0187] like Figure 3 and Figure 4 As shown, the hammer structure adopts an innovative combined structure. The hammer structure 100 includes a hammer body 110 and a wear-resistant component 120. The hammer body 110 is rectangular in shape, with a stepped mounting portion 111 at the upper end and a limiting groove 112 in the mounting portion. The wear-resistant component 120 has a limiting portion 121 that fits into the limiting groove 112. The wear-resistant component 120 is inserted into the limiting groove 112 through the limiting portion 121, and the wear-resistant component can also be fastened to the mounting portion of the hammer body by bolts. Both the hammer body 110 and the wear-resistant component 120 are made of wear-resistant alloy steel.
[0188] In this application, the main body of the hammer is in the shape of a cuboid block. This structural design ensures that the hammer has a large bearing area and good structural stability when subjected to strong impact.
[0189] In one specific implementation, a stepped mounting section is provided at the upper end of the hammer body. This design helps to enhance the connection between the hammer and the wear-resistant parts and optimize their force distribution. The stepped mounting section provides a larger contact area, which helps to evenly distribute the impact force received by the hammer during operation. A limiting groove is provided in the mounting section. This design ensures the precise positioning of the wear-resistant parts and also prevents the wear-resistant parts from shifting or loosening during operation.
[0190] In this application, the wear-resistant part has a limiting portion that matches the limiting groove. By inserting the limiting portion into the limiting groove, a mechanical connection is formed between the wear-resistant part and the hammer body, ensuring that the wear-resistant part will not shift during the operation of the impact crusher. Furthermore, the wear-resistant part is also connected to the mounting portion of the hammer body by bolt fastening. For example, the limiting groove is a dovetail tenon, and the limiting portion is a matching dovetail tenon. Specifically, the limiting groove is partially formed on one side of the top of the hammer body, with the groove opening located on the outer wall of the hammer body. During installation, simply align the limiting portion of the wear-resistant part with the opening of the limiting groove, push the wear-resistant part in until it is fully inserted, and then tighten the bolts.
[0191] Specifically, the bolted connection ensures that the wear-resistant parts can be stably bonded to the hammer body for a long time under high impact and high wear environments, and are not easy to fall off. For example, spring washers are provided at the bolted connection.
[0192] Understandably, the use of bolts to fasten the wear-resistant parts to the hammer body makes replacement much easier. Wear-resistant parts can be quickly disassembled and replaced simply by loosening the bolts, significantly reducing downtime and maintenance costs. The modular design means that replacing or repairing the hammer body and wear-resistant parts does not require replacing the entire hammer, thus reducing maintenance costs and resource waste.
[0193] To address this, the hammer structure provided by this invention employs an innovative combined structural design to tightly integrate the hammer body and wear-resistant components. Utilizing techniques such as limiting grooves, limiting parts, and bolt fastening connections, the stability and robustness of the wear-resistant components are ensured. Furthermore, replacement is simple: only the damaged wear-resistant component needs to be removed, and a new one installed, making the entire process convenient and efficient. This significantly improves the hammer's wear resistance, impact resistance, and overall working efficiency. On the other hand, the innovative wear-resistant alloy steel material provides superior hardness and wear resistance, enabling a longer service life in high-impact, high-wear working environments.
[0194] In one specific implementation, the cross-sectional profile of the wear-resistant part is a right-angled trapezoidal shape, and the wear-resistant part has an outer surface for contacting materials. The outer surface of the wear-resistant part can be straight, inclined, or curved. A wear-resistant coating is provided on the outer surface of the wear-resistant part.
[0195] Understandably, the cross-sectional profile of the wear-resistant part is a right-angled trapezoid. This design makes the installation and fixation of the wear-resistant part more stable, reducing the possibility of relative slippage or loosening during installation. The outer surface of the wear-resistant part is the part that contacts the material, and it can be designed with different shapes, for example:
[0196] (1) Flat type: suitable for conventional crushing operations, providing a uniform wear surface and increasing wear resistance.
[0197] (2) Inclined surface: This design helps to better withstand the impact of materials and improve crushing efficiency, especially suitable for crushing harder or larger materials.
[0198] (3) Arc-shaped: Arc-shaped surfaces can effectively reduce stress concentration during impact, improve wear resistance, and help improve the distribution effect of materials. They are suitable for high impact and high load environments.
[0199] The wear-resistant component of this invention has a right-angled trapezoidal cross-sectional profile and an adjustable shape (straight, inclined, or curved) to suit different working conditions, thereby improving the wear resistance of the impact crusher hammer. The use of a wear-resistant coating further enhances the wear resistance of the component and extends its service life.
[0200] In a preferred embodiment, the wear-resistant coating is a gradient structure coating, which has a bonding layer, a load-bearing layer and a wear-resistant layer formed sequentially by laser cladding process, and the bonding layer is connected to the outer surface of the wear-resistant part.
[0201] In some specific implementations, the wear-resistant coating is a wear-resistant gradient alloy steel coating prepared based on laser deposition technology. This coating has a gradient characteristic of "external strength and internal toughness", which can meet the performance requirements of the impact crusher hammer under high-energy impact and strong abrasive wear environment. The coating is divided into three functional gradient structures: (1) bonding layer: connected to the main body of the hammer, providing good adhesion and toughness. (2) bearing layer: connecting the bonding layer and the wear-resistant layer, buffering the impact force, and ensuring a balance between medium hardness and toughness. (3) wear-resistant layer: the outermost layer, providing high hardness and high wear resistance, and withstanding direct material impact and abrasive wear.
[0202] For example, the bonding layer has the following material composition (wt%): C 0.20%, Ni 2%, Cr 1.5%, Mo 0.2%, Fe balance. This bonding layer provides toughness, reduces thermal expansion mismatch and residual stress between the coating and the substrate, and improves bonding strength. The load-bearing layer has the following material composition (wt%): C 0.45%, Cr 6%, Ni 2%, Al 0.2%, Fe balance. It mainly supports the outer wear-resistant layer, absorbs impact energy, and possesses moderate hardness and toughness. The wear-resistant layer has the following material composition (wt%): C 1%, Cr 12%, Ni 2%, Ti 1%, B 0.5%, Fe balance. During laser deposition, Ti and B form an in-situ TiB2 ceramic reinforcing phase, improving surface hardness and wear resistance while ensuring stable bonding under impact.
[0203] In some specific implementations, this application also provides process parameters for the laser deposition technology of wear-resistant coatings, as shown in the table below:
[0204] bonding layer 2000 W 5 mm / s 100 g / min 5% 100 Bearing layer 2000 W 5 mm / s 100 g / min 5% 100 wear-resistant layer 1900 W 5 mm / s 40 g / min 6.5% 95
[0205] In one specific implementation, the preparation process of the wear-resistant coating includes:
[0206] (1) Substrate preparation: Before starting deposition, the surface of the wear-resistant part is polished and cleaned.
[0207] (2) Bonding layer deposition: Using the above laser process parameters, deposit 10 layers, each with a thickness of 0.5 mm, to form a bonding layer.
[0208] (3) Deposition of the carrier layer: Replace the powder with the carrier layer material and deposit 5 layers, each with a thickness of 0.5 mm.
[0209] (4) Wear-resistant layer deposition: Replace the powder with wear-resistant layer material and deposit 3 layers, each with a thickness of 0.5 mm.
[0210] (5) Cooling treatment: After deposition, natural cooling or low temperature stress relief treatment is performed to eliminate internal stress and stabilize the coating structure.
[0211] It should be noted that the coating exhibits a gradient distribution in its microstructure, with the following morphologies for each layer: Bonding layer: primarily low-carbon martensite with a small amount of bainite, possessing high toughness and good adhesion. Load-bearing layer: primarily lath bainite, with moderate hardness and good toughness, capable of buffering impact forces. Wear-resistant layer: primarily lath martensite and plate martensite, with distributed nano-TiB2 ceramic particles, providing high hardness and wear resistance while preventing crack propagation.
[0212] In this embodiment, the wear-resistant coating has a gradient hardness distribution across its layers, with the surface wear-resistant layer having a hardness of approximately 700–720 HV0.2, the load-bearing layer having a hardness of approximately 500–550 HV0.2, and the core bonding layer having a hardness of approximately 350–370 HV0.2. The overall flexural strength of the coating is not less than 1420 MPa, exhibiting excellent wear resistance, and the volumetric wear rate of the surface wear-resistant layer is less than or equal to 0.71 × 10⁻⁻⁻⁶. 4 mm³·N⁻¹·m⁻¹, achieving a performance gradient of external strength and internal toughness.
[0213] like Figures 1-4 As shown in the embodiment of this application, a crushing chamber structure is also provided for an impact crusher 10. The crushing chamber structure includes:
[0214] The frame includes an upper frame and a lower frame that are arranged to cooperate with each other. One side of the lower frame is open. The upper frame is installed in the open part of the lower frame. The upper frame and the lower frame are closed to form a crushing chamber. The crushing chamber has a material feed end and a material discharge end.
[0215] The rotor assembly includes a rotor and multiple hammers. The rotor is rotatably mounted on the lower frame and located in the crushing chamber. The multiple hammers are detachably mounted on the rotor and are evenly distributed along the circumference of the rotor. The hammers adopt the hammer structure described above.
[0216] The impact plate assembly 200 includes multiple impact frames and multiple impact plates connected to the impact frames; the multiple impact frames are arranged sequentially along the outer circumferential surface of the rotor; the multiple impact plates are arranged at intervals along the outer circumferential direction of the rotor, and a crushing chamber is formed between the multiple impact plates and the rotor.
[0217] In this application, because the hammer plate uses detachable wear-resistant parts and a gradient wear-resistant coating, the wear-resistant parts can be replaced individually according to the wear condition, eliminating the need to replace the entire hammer plate, thus improving the utilization rate of metal materials and reducing maintenance costs. The gradient wear-resistant coating, combined with in-situ hard phase reinforcement, gives the hammer plate high hardness, high toughness, and anti-stripping properties under impact and abrasive wear, thereby improving the overall production efficiency and service life of the impact crusher.
[0218] In this embodiment, the frame includes an upper frame and a lower frame that cooperate with each other. One side of the lower frame has an open structure, and the upper frame is closably installed at the open portion of the lower frame, allowing the upper frame to open or close relative to the lower frame. When the upper and lower frames are in the closed state, they together form a crushing chamber, which has a material inlet and a material outlet along the material flow direction.
[0219] In this embodiment, the rotor assembly includes a rotor and multiple hammers. The rotor is rotatably mounted on the lower frame and is entirely located within the crushing chamber. Driven by a drive unit (such as a motor and transmission mechanism) of the impact crusher, the rotor rotates at high speed around its own axis. Multiple hammers are detachably mounted on the rotor, and are evenly distributed along the circumference of the rotor. This detachable mounting method allows for individual replacement of worn hammers, reducing maintenance costs.
[0220] In this embodiment, the impact plate assembly 200 includes multiple impact frames and multiple impact plates connected to each impact frame. The multiple impact frames are located on the outside of the rotor and arranged sequentially along the outer circumference of the rotor. Each impact frame is arranged in a ring around the rotor, such that the impact plate assembly partially covers the outer circumference of the rotor. The multiple impact plates are spaced apart along the outer circumference of the rotor, and the impact plates and the rotor enclose a crushing chamber. The crushing chamber is the main space for material movement and stress during the crushing process. The impact plates are fixedly mounted on their corresponding impact frames, and each impact frame is used to bear and support the impact plates, enabling the impact plates to withstand multiple impacts from the material during the crushing process.
[0221] During operation, material enters the crushing chamber from the feed end. Driven by the drive unit, the rotor rotates at high speed, and the hammers on the rotor rotate with it, generating a high-speed impact on the material entering the crushing chamber. After the initial impact from the hammers, the material is thrown towards the impact plate assembly 200 and collides with it. Subsequently, the material bounces and impacts repeatedly between the hammers and the impact plates, gradually undergoing crushing. During this process, the impact plate assembly 200, forming a crushing chamber around the rotor, restricts and guides the material's trajectory, subjecting it to multiple impacts, shearing, and compression within the crushing chamber, thus achieving effective crushing.
[0222] In this embodiment, the hammer adopts the aforementioned hammer structure (i.e., the hammer structure described in the previous embodiment). This hammer structure can maintain good structural strength and wear resistance under high-speed impact conditions, thereby ensuring the reliability of the rotor assembly during long-term operation.
[0223] With the aforementioned openable frame, the crushing chamber structure allows the upper frame to be opened when it is necessary to inspect or replace the rotor assembly, hammer, or impact plate, thereby exposing the internal structure of the crushing chamber, facilitating maintenance operations and improving the maintainability of the equipment.
[0224] like Figure 2As shown, in one specific embodiment, the impact plate assembly includes three impact frames arranged sequentially along the material feed end to the material discharge end, and the length of the three impact frames decreases sequentially along the material feed end to the material discharge end; the impact plates set on each impact frame are distributed in a logarithmic spiral shape with the rotor axis as the center, so that multiple impact plates gradually approach the outer circumference of the rotor along the material feed end to the material discharge end, thereby forming a cavity structure in which the crushing chamber gradually contracts from the feed end to the discharge end.
[0225] In this embodiment, the impact plates of the crushing chamber structure are not arranged along a constant-diameter circular arc or a linear contraction curve, but rather with the rotor axis as the geometric center, gradually approaching the rotor according to a logarithmic spiral law. Because the logarithmic spiral has the geometric characteristic that "the radial contraction rate has a non-linear relationship with the circumferential angle," the radial distance between the impact plate and the rotor axis changes more smoothly and continuously during the circumferential extension process, thus avoiding the local abrupt change regions present in traditional equal-spaced impact plates or linear contraction chamber types.
[0226] During the crushing process, after the material enters the crushing chamber from the feed end, it is first subjected to the high-speed impact of the hammers on the rotor and then thrown against the impact plate located on one side of the feed end. Due to the large distance between the impact plate and the rotor at the feed end, the material gains a large space to move within this area, which is beneficial for primary crushing. As the material moves towards the discharge end along the crushing chamber under the impact of the hammers and the rebound of the impact plate, the radial distance between the impact plate and the rotor axis gradually decreases, causing the crushing chamber to gradually contract. The impact frequency and compression degree experienced by the material during its movement gradually increase, thus achieving a continuous crushing process of medium and fine crushing. Compared to constant-diameter impact plates or linear contraction chamber structures, this logarithmic spiral crushing chamber allows for a smoother material trajectory, more uniform release of impact energy, and reduces ineffective accumulation and excessive impact of material in local areas. This effectively improves the finished product particle shape and reduces over-crushing while ensuring crushing efficiency.
[0227] The crushing chamber structure of this application, through the optimized arrangement of the impact frame and impact plate, allows for more efficient crushing and impact of materials within the crushing chamber, ensuring that the crusher maintains high crushing efficiency under different material handling conditions. The tapered crushing chamber shape helps to distribute the force evenly on the material and reduces unstable crushing caused by uneven material distribution within the chamber.
[0228] In a preferred embodiment, the impact plate is made of the same wear-resistant alloy steel as the hammer structure.
[0229] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. For those skilled in the art, it will be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A wear-resistant alloy steel for crushers, specifically for the hammer plates of an impact crusher, characterized in that... The wear-resistant alloy steel is made of a matrix material compounded with ZTA ceramic particles, wherein the volume fraction of the ZTA ceramic particles in the wear-resistant alloy steel is 20% to 25%; wherein the matrix material comprises the following raw materials by weight percentage: C 0.50~0.55%; Si 0.9–1.2%; Mn 0.9–1.1%; Cr 0.9~1.2%; Mo 0.4–0.6%; Ni 1.6~1.8%; Nb 0.18%; The balance is Fe; The ZTA ceramic particles have a particle size of 1-2 mm and are pretreated and modified using the following method: ZTA ceramic particles were placed in an ultrasonic cleaner and ultrasonically cleaned with anhydrous ethanol for 30 minutes. The cleaning was repeated 3 times. After cleaning, the ZTA ceramic particles are placed in an oven for drying at 80℃ for 1 hour. Cleaned and dried ZTA ceramic particles, PVA binder, and Ti-Cu-Ni powder were added to a vibrating ball mill and mixed for 3 minutes to allow the Ti-Cu-Ni powder to adhere to and coat the surface of the ZTA ceramic particles. The amount of PVA binder added was 2.0 wt% of the mass of the ZTA ceramic particles, and the amount of Ti-Cu-Ni powder added was 8.0 wt% of the mass of the ZTA ceramic particles. The mass ratio of Ti, Cu, and Ni in the Ti-Cu-Ni powder was 4:3:
3. Alloy powder is prepared, wherein the raw materials and proportions of the alloy powder are the same as those of the matrix material; ZTA ceramic particles coated with Ti-Cu-Ni powder are mixed with the alloy powder in a vibrating ball mill for 3 minutes to further coat the outer layer of the ZTA ceramic particles with the alloy powder; wherein the amount of alloy powder added is 8.0 wt% of the mass of the ZTA ceramic particles.
2. The wear-resistant alloy steel for crushers according to claim 1, characterized in that, The ZTA ceramic particles have a volume fraction of 25%; the matrix material is composed of the following raw materials by weight percentage: C 0.50%; Si 1.0%; Mn 1.0%; Cr 1.1%; Mo 0.5%; Ni 1.7%; Nb 0.18%; The balance is Fe.
3. The wear-resistant alloy steel for crushers according to claim 2, characterized in that, The wear-resistant alloy steel is prepared by the following method: Step 1: Mix the pretreated and modified ZTA ceramic particles with the matrix material according to the preset ratio, and obtain composite powder after uniform mixing; Step 2: The composite powder is loaded into the cavity of the pre-made mold and subjected to hot isostatic pressing at a temperature of 900℃ and a pressure of 150MPa to obtain a preliminary blank. Step 3: The preliminary blank is sintered under an argon protective atmosphere at a sintering temperature of 1150℃ for 3 hours to obtain a sintered blank. Step 4: Heat treatment of the sintered billet, including normalizing, quenching and tempering; specifically, normalizing involves heating to 1000℃, holding for 6 hours, and air cooling to room temperature; quenching involves heating to 900℃, holding for 6 hours, and then quenching with PAG quenching liquid; tempering involves tempering at 330℃, holding for 8 hours, and then air cooling to room temperature.
4. A hammer plate structure for an impact crusher, characterized in that, The hammer structure is made of wear-resistant alloy steel for crushers as described in claim 3.
5. The hammer plate structure according to claim 4, characterized in that, The hammer structure adopts a combined structure, including: The hammer body is in the shape of a cuboid block, and has a stepped mounting part at the upper end of the hammer body, and a limiting groove is provided in the mounting part. The wear-resistant part has a limiting part that is adapted to the limiting groove. The wear-resistant part is inserted into the limiting groove through the limiting part, and the wear-resistant part can also be fastened to the mounting part of the hammer body by bolts. The hammer body and wear-resistant parts are both made of the wear-resistant alloy steel.
6. The hammer plate structure according to claim 5, characterized in that: The wear-resistant part has a right-angled trapezoidal cross-sectional profile and an outer surface for contacting materials. The outer surface of the wear-resistant part can be straight, inclined, or curved. A wear-resistant coating is provided on the outer surface of the wear-resistant part.
7. A hammer plate structure according to claim 6, characterized in that: The wear-resistant coating is a gradient structure coating, which has a bonding layer, a load-bearing layer and a wear-resistant layer formed sequentially by laser cladding process, and the bonding layer is connected to the outer surface of the wear-resistant part.
8. A crushing chamber structure, applied to an impact crusher, characterized in that, The crushing chamber structure includes: The frame includes an upper frame and a lower frame that are arranged to cooperate with each other. One side of the lower frame is open, and the upper frame is detachably installed at the opening of the lower frame. The upper frame and the lower frame are closed to form a crushing chamber, which has a material inlet end and a material outlet end. A rotor assembly includes a rotor and a plurality of hammer plates. The rotor is rotatably mounted on the lower frame and located in the crushing chamber. The plurality of hammer plates are detachably mounted on the rotor and are evenly distributed along the circumference of the rotor. The hammer plates adopt the hammer plate structure according to any one of claims 4 to 7. The impact plate assembly includes multiple impact frames and multiple impact plates connected to the impact frames; the multiple impact frames are arranged sequentially along the outer circumferential surface of the rotor; the multiple impact plates are arranged at intervals along the outer circumferential direction of the rotor, and a crushing chamber is formed between the multiple impact plates and the rotor.
9. The crushing chamber structure according to claim 8, characterized in that: The impact plate assembly includes three impact frames arranged sequentially along the material feed end to the material discharge end, and the length of the three impact frames decreases sequentially along the material feed end to the material discharge end. The impact plates installed on each impact frame are arranged in a logarithmic spiral shape with the axis of the rotor as the center, so that multiple impact plates gradually approach the outer circumference of the rotor along the direction from the material feed end to the material discharge end, thereby forming a cavity structure in which the crushing chamber gradually contracts from the feed end to the discharge end.
Citation Information
Patent Citations
Martensite / bainite steel-based ZTA ceramic composite material impact crusher plate hammer and manufacturing method thereof
CN114570483A
Construction method and application of gradient metallurgical composite interface between ZTA ceramic particles and alloy steel matrix
CN119794333A
Safe type backstroke crusher
CN201064725Y
Double-panel hammer with conveniently replaced striking block
CN212855998U
Non-heattreated steel for induction hardening
JP1988100157A